Development and validation of nomogram for prediction of malignant transformation in oral leukoplakia: A large‐scale cohort study. (15th May 2019) - Wang, Tianjiao; Wang, Lin; Yang, Huifang; Lu, Han; Zhang, Jianyun; Li, Nan; Guo, Chuan‐Bin
Abstract: Purpose: Oral leukoplakia (OL) is the well‐known disorder of oral mucosa, which has potential to be malignant and can lead to squamous cell carcinoma (OSCC). In the following study, we developed a comprehensive nomogram for predicting the malignant progression of OL, based on analysis of clinicopathological variables. Methods: A retrospective analysis of patients diagnosed with OL was performed between 1998 and 2017 at the Peking University School and Hospital of Stomatology. OL was confirmed by pre‐treatment biopsy. The candidate risk factors for OL malignant transformation were screened from clinicopathological variables using the Cox proportional hazard regression analysis. The nomogram model was generated based on the COX regression results and was validated through Harrell concordance index (c‐index) and calibration plots Results: The incidence of OL malignant transformation (MT) was 12.2% (107/875), and the mean follow‐up time was 4.5 years. The risk factors (age, histologic grade, site of lesion and smoking habit) derived from Cox proportional hazard regression analysis were incorporated in a novel nomogram model for prediction of MT severity. The c‐index value of the nomogram model was 0.752, which confirmed the prediction ability; and was further confirmed by calibration plots results. Conclusion: Our data suggest that patients with OL who are over 50 years old, non‐smokers with dysplasia, and OL lesions involving the lip, the floor of mouth, and tongue have an enhanced risk of MT. The established nomogram model has the predictive value of malignant progression, which is conductive to screen high‐risk patients and guide treatment strategy.